Critical Analysis of New Weapons Technologies - Altmann, Jürgen (Peace review (Palo Alto, Calif.), 2009)
The use of new technology has become a decisive factor in war, & thus modern armed forces spend a great deal of effort on military research & development. In many cases, however, new military technologies have made the participants in arms races less secure, & have rendered the attainment of peace more fragile. Decisions for the development of these technologies can be biased by unrealistic expectations of their effectiveness, & there are even cases where research has continued, despite a clear lack of any scientific foundation. Adapted from the source document.